iGuide - United Nations Department of Economic; Social Affairs (United Nations, 2013)
The iGUIDE is the first-ever comprehensive resource directory of local Information and Communication Technologies and Development (ICTD) initiatives. Its easy-to-use listings of vital information about ICTD organizations and ICTD founders will serve as a valuable resource for ICTD practitioners, not only in Silicon Valley and the San Francisco Bay Area, but also internationally. The iGUIDE will furthermore serve as a blueprint for replication in other areas of the world where ICTD is of growing importance to meet the global challenge to realize the Millennium Development Goals.